Analysis of the Rational Use of Antibiotics in Cases of Respiratory Tract Infections at Siti Fatimah Regional General Hospital - Anggy Utama Putri; Diah Ayu Setiani; Rahayu Wijayanti (CV. AFDIFAL MAJU BERKAH, 2026)
Acute Respiratory Tract Infections (ARI) are a leading cause of morbidity and mortality worldwide, with often irrational antibiotic use risking resistance. This study aims to analyze the rationality of antibiotic use in ARI patients at Siti Fatimah Provincial Hospital, Palembang, in 2024. This study used a quantitative descriptive design with a cross-sectional method. Data were obtained retrospectively from the medical records of inpatients who met the inclusion criteria from January to December 2024. Rationality analysis was conducted based on appropriate indication, appropriate drug, appropriate dose, appropriate patient, appropriate duration of administration, and appropriate diagnosis, in accordance with WHO standards and antibiotic therapy guidelines. The results showed that the overall accuracy rate was quite good, with 99% of patients receiving antibiotics according to their diagnosis, 95% receiving the appropriate dose, 100% receiving the appropriate indication, 100% receiving the appropriate type, 100% receiving the appropriate duration, and 100% receiving the appropriate patient.